(untitled) (MMIT Proceedings, 2025)
This article explores the profound role of Artificial Intelligence (AI) as a key driver of modern innovation management, transforming industries and national economies through automation, data-driven decision-making, and efficiency optimization. It examines AI’s significant impact on sustainable development and technology within Uzbekistan’s economic ecosystem, highlighting how AI integration is reshaping both the public and private sectors. The Uzbek government’s AI Strategy 2030 envisions the widespread adoption of intelligent technologies to enhance public services, stimulate entrepreneurship, and modernize vital industries such as finance, agriculture, energy, and healthcare. As AI becomes an integral part of the nation’s digital infrastructure, Uzbekistan’s corporate landscape is undergoing rapid transformation. Using data from 2021 to 2025, the paper analyzes how AI contributes to financial growth and operational performance among Uzbek enterprises. It also presents two detailed business case studies demonstrating practical AI applications, followed by targeted recommendations and strategies to overcome implementation challenges. Ultimately, this research emphasizes AI’s transformative potential in emerging markets and outlines a strategic roadmap toward sustainable, technology-driven economic growth in Uzbekistan